2005
DOI: 10.2174/1389557053175344
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxotungstates Reduce the β-Lactam Resistance of Methicillin-Resistant Staphylococcus aureus

Abstract: Bacterial strains isolated from clinical specimens have become more and more resistant to many anti-microbials. This is because we have consumed large amounts of strong antimicrobials over long periods of time and thus bacterial cells are able to survive by altering the target(s) of antimicrobial agents. A good example of this phenomenon is methicillin-resistant Staphylococcus aureus (MRSA). One of the cell wall-synthesizing enzymes (known as PBP2') of this pathogen has low affinity to beta-lactams, and theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 97 publications
(246 reference statements)
0
5
0
Order By: Relevance
“…The mechanism responsible for this phenomenon is probably the stress response of MRSA to POT. Sensitization to beta-lactams was also seen with other substances such as fosfomycin, Triton X-100, tannin and some flavonoids (Tajima, 2005).…”
Section: B Old Medications -New Usesmentioning
confidence: 89%
“…The mechanism responsible for this phenomenon is probably the stress response of MRSA to POT. Sensitization to beta-lactams was also seen with other substances such as fosfomycin, Triton X-100, tannin and some flavonoids (Tajima, 2005).…”
Section: B Old Medications -New Usesmentioning
confidence: 89%
“…Polyoxometalates (POMs) have been shown to exhibit biological activities in vitro as well as in vivo , including anticancer and antiviral [1], antibacterial [2, 3], antiprotozoal [4, 5], and antidiabetic activities [6]. In the antibacterial activity study of POMs, Tajima found the enhancement of several beta-lactams antibiotics in antibacterial activity to methicillin-resistant Staphylococcus aureus under the synergistic action of polyoxometalates, substituted-type POMs K 7 [PTi 2 W 10 O 40 ] 6H 2 O, K 7 [BVW 11 O 40 ]7H 2 O, [SiFeW 11 O 40 ] 6/5− and [SiCoW 11 O 40 ] 6− and lacunary-type POMs [XW 11 O 39 ] n− (X = Si, P) and [XW 9 O 34 ] n− , and proposed the resistant mechanism [712]. Inoue et al reported the enhancement of antibacterial activity of beta-lactam antibiotics, oxacillin, by polyoxometalates (K 6 [P 2 W 18 18O 62 ]·14H 2 O, K 4 [SiMo 12 O 40 ]·3H 2 O, and K 7 [PTi 2 W 10 O 40 ]·6H 2 O) against methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant S. aureus (VRSA) and also proposed a reaction mechanism [13].…”
Section: Instructionmentioning
confidence: 99%
“…These physiological effects associated with phosphorous-POTs include inhibition of factors IIa and Xa in the presence of anti-thrombin III and inhibition of anion-transport in erythrocytes and porcine sperm. The WO 4 2ion did not exhibit these traits (reviewed in Tajima 2005).…”
Section: Tungstate-associated Suppression Of Dmbt1mentioning
confidence: 99%